Impact of microvascular integrity and local viability on left ventricular remodelling after reperfused acute myocardial infarction. Issue 4 (1st April 2003) - Garot, P; Pascal, O; Simon, M; Monin, J L; Teiger, E; Garot, J; Guéret, P; Dubois-Randé, J L
Abstract : Objective: To assess left ventricular remodelling in patients with reperfused acute myocardial infarction and to study its relation to microvascular damage. Patients: 25 patients successfully treated by primary percutaneous coronary angioplasty for acute myocardial infarction. Setting: University hospital Methods: Indexed end diastolic (EDVi) and end systolic (ESVi) volumes were assessed on admission and repeated at days 1 and 8. Coronary flow reserve (CFR) was assessed in the infarct related artery on day 1. Myocardial blood volume was assessed on admission and at day 8 by myocardial contrast echocardiography. In patients who manifested persistent myocardial dysfunction at hospital discharge (n = 21), local inotropic reserve was assessed by dobutamine echocardiography at day 7. Results: On admission, patients with and without local viability had similar EDVi and ESVi (EDVi 67 (9) and 73 (14) ml/m 2, respectively; ESVi 34 (8) and 40 (11) ml/m 2, respectively; NS). EDVi increased to 97 (22) ml/m 2 in patients without local viability (p < 0.01 v admission) but remained unchanged at 70 (11) ml/m 2 in patients with viable myocardium (NS v admission). For pooled patient data, the percentage change in EDVi correlated with CFR ( r = 0.76, p < 0.0001) and myocardial blood volume in the infarct territory ( r = 0.80, p < 0.0001). Conclusion: Left ventricular dilatation may preferably occur in patients without local viability and is correlated with early CFR and extent of myocardial blood volume in the infarct territory.